2013
DOI: 10.1108/ap-11-2012-0088
|View full text |Cite
|
Sign up to set email alerts
|

A spatial exploration of factors affecting digitalization of farmers' associations in Taiwan

Abstract: Purpose -This study aimed to examine organizational digitalization of farmers' associations (FAs) by conducting internal and external analyses of the contextual and geo-spatial attributes of the organizations, and further explored the role such associations play as key change agents in activating agricultural innovations and development in Taiwan. Design/methodology/approach -Unlike previous digitalization studies, which employed user data such as attitudes and behaviors as the major determinants, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These results align with the findings from Yueh et al. (2013) on the size of farmers’ associations. The variables representing productive characteristics, geographical location, and productive assets do not show a significant correlation with internet use in agricultural cooperatives (except for the number of water pumps).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results align with the findings from Yueh et al. (2013) on the size of farmers’ associations. The variables representing productive characteristics, geographical location, and productive assets do not show a significant correlation with internet use in agricultural cooperatives (except for the number of water pumps).…”
Section: Resultssupporting
confidence: 92%
“…Regarding the factors affecting internet use, empirical evidence is available with household data (for example, Chang & Just, 2009;Mishra & Park, 2005;Nguyen & Do, 2022;Yang et al, 2021), but only a few with cooperative data (Cristobal-Fransi et al, 2020;Dholakia & Kshetri, 2004). These studies showed that fixed assets, the number of laborers (size), and the fields of business were key variables affecting cooperatives' digitalization, while external factors such as regional indicators did not have a significant correlation with the digitalization (Hejkrlik et al, 2021;Yueh et al, 2013). Khanal et al (2015) found that the operator's age had a negative correlation, while the operator's education was positively correlated with internet adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the impact of digitalization on cooperatives was raised by Yueh, Chen, & Chen (2013). This study explored farmers' associations in Taiwan using spatial analysis.…”
Section: Literature Reviewmentioning
confidence: 99%